Development Of Learning Multimedia In Mathematics Subjects For Grade III Elementary School Students - Rosman, Zaidinatul; Hidayati, Abna (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
The background of this research is due to several facts found in the field. This is because students have difficulty understanding the concept of multiplication and division and students have difficulty understanding multiplication and division of two-digit numbers. This study aims to produce learning multimedia products in Mathematics class III SD that are valid, practical, and effective.This type of research is development research known as Research and Development (R&D), using the 4-D development model. The development procedure in this study consisted of 4 stages namely; (1) Define, (2) Design, (3) Develop, (4) Disseminate. The product validity test was carried out by 3 validators, namely 1 material expert validator and 2 media expert validators. Product trials were carried out on 20 third grade students at SD Negeri 27 Limau Asam with the aim of knowing the practicality and effectiveness of the product being developed. Development of learning multimedia, the results of which were assessed by 2 material and media validators, each of which was categorized as "very valid", which scored 92.30% for material, and 95.71% for media, but there were several revisions to material and media . The results of the practicality trial analysis obtained an average value of 91.87% so that learning media products were in the very practical category. The effectiveness test that has been carried out shows t count > t table so that it shows a significantly higher difference between pretest and posttest. These results indicate that this product is effective and can be used. Based on the results of the validity, practicality, and effectiveness tests, it can be concluded that the learning media produced are feasible so that they can be used in Mathematics Class III SD. This learning multimedia can also improve learning outcomes, it is proven that student learning outcomes have increased from pretest to posttest scores.